Impact of a Women‐focused Professional Organization on Academic Retention and Advancement: Perceptions From a Qualitative Study. (19th February 2019) - Lin, Michelle P.; Lall, Michelle D.; Samuels‐Kalow, Margaret; Das, Devjani; Linden, Judith A.; Perman, Sarah; Chang, Anna Marie; Agrawal, Pooja
Abstract: Objectives: Organizations to promote career networking and mentorship among women are recommended as a best practice to support the recruitment and retention of women physicians; however, the impact of such organizations is unknown. Our primary objective is to describe the impact of a national woman‐focused organization for academic emergency physicians on retention and advancement. Methods: We conducted semistructured interviews of past and present organization leaders, as well as members at varying stages in their careers. Physicians with experience in qualitative methods conducted interviews and coded all transcripts using inductive content analysis techniques. Themes were reviewed and discussed to ensure consensus. Results: We performed 17 interviews lasting 20 to 30 minutes each, resulting in 476 total minutes of transcript. Participants represented varying stages of career experience, ranging from 2 to 35 years since residency completion (median = 9.5 years). Median years of participation in the woman‐focused organization was 10 years. Over half (53%) of participants were past presidents of the organization. The dominant themes encompassed facilitating academic advancement through scholarly productivity, leadership experiences, awards, and promotions; mentorship and sponsorship; peer support and collaborations; reduced professional isolation; and initiatives to address systemic gender inequities and challenges, including strategies to navigate bias, promote pay equity, and advocate for family‐friendly workplace policies. Discussion: Active participation in a woman‐focused professional organization enhances members' career retention and advancement by creating opportunities and relationships that facilitate leadership, enabling scholarly work to advance equity and inclusion, and cultivating a sense of belonging. While challenges and barriers persist, the myriad benefits of a women‐focused professional organization reported by members and leaders represent important steps toward greater equity for women and other underrepresented groups in academic medicine.